Ancient scholarship on papyrus: new light from Oxyrhynchus - Panegyres, K (2022)
This thesis presents editions of twenty-one previously unpublished papyri from the Oxyrhynchus Papyri collection in the Sackler Library, Oxford. Every papyrus is edited with introduction, commentary, and translation, according to the conventions of The Oxyrhynchus Papyri (London, 1898–). All the papyri deal in some way with ancient scholarship. There are new commentaries on Homer, Apollonius Rhodius, and Herodotus; new grammatical treatises dealing with the letters of the alphabet, with nouns/adjectives, with doxography, and with various other matters; new scholia minora on the Iliad and the Odyssey; new texts displaying ancient marginal annotations; and a few miscellaneous pieces dealing with mythography， biography, and other varied subjects. These papyri bring to light interesting evidence. There are new testimonia for ancient scholars, including Philitas of Cos, Zenodotus of Ephesus, Apollodorus of Athens, Istrus of Paphos, and Aristonicus of Alexandria. There are also new citations of classical literature, including a superior text of Alcman, PMG fr. 80, and references to lost works of drama, Euripides’ Tennes and Sophocles’ Tereus. The main significance of these papyri lies however in the extent to which they enlarge the current state of knowledge about scholarship in the Roman period. Some pieces, such as the commentary on Herodotus, provide rare and substantial new evidence for ancient scholarship on a particular author, while others, such as the scholia minora, contribute usefully to the stock of evidence for types of ancient scholarship that are already well known.